Uji Kinerja Alat Pemotong Bibit Singkong (Petokong) Tipe TEP-1 Menggunakan Batang 3 Varietas Tanaman Singkong - Haryono, Yudi; Asmara, Sandi; Kuncoro, Sapto; Tamrin, Tamrin (Jurnal Agricultural Biosystem Engineering, 2022)
Preparation of cassava seedlings (cuttings) is usually done manually by farmers using slash or hand saws which are considered less effective today. With these problems, TEP-1 Type Cassava Seed Cutting Tool was made as a solution in the effort to meet the needs of cassava seedlings whose performance needs to be tested on several types and varieties of cassava plants. In this study a completely factorial completely randomized design (RALF) method was used using two treatment factors. The first treatment factor is the cutting machine RPM tested at three levels including the RPM 3500, RPM 4000, and RPM 4500. The second treatment factor is the cassava plant varieties tested at three levels, namely by using Kasetsart varieties, Thailand varieties, and Garuda varieties. The test results were analyzed by analysis of variance using the SAS program. The working capacity of Petokong tools in the Kasetsart variety is 9900 seedlings / hour at RPM 3500, 10620 seeds / hour at 4000 RPM, and 11340 seedlings / hour at RPM 4500. While in Thailand varieties, the working capacity of Petokong tools is 5500 seedlings / hour at RPM 3500 , 8250 seedlings / hour at 4000 RPM, and 8700 seedlings / hour at 45,000 RPM. The working capacity of the Butters in the Garuda variety is 5220 seeds / hour at 3500 RPM, 6300 seedlings / hour at 4000 RPM, and 7020 seeds / hour at 4500 RPM. Based on analysis of variance, the interaction between engine RPM factors and cassava varieties did not significantly affect work capacity, fuel consumption, and the level of uniformity of the performance results of the Supporting Equipment. Keywords: Cassava, Cassava Seedlings, Petokong, Work Capacity.